Measles Outbreak in Sleman 2024 - Maziyya, Arifah Alfi; Assaad, Andi Ratu Boelqiah; Khoirunnisa; Hidayat, Wachid Nur; Dharmawidjaja, Isa; Oktaria, Vicka (BKM Public Health and Community Medicine, 2024)
Purpose: On January 18th, 2024, the Sleman District Health Office received a notification from Sleman Regional Hospital regarding the presence of 2 measles suspects in 1 family in Pakem, Sleman. This study aims to confirm the outbreak and know its management in Sleman, 2024. Method: A descriptive study was conducted based on person, place, and time. An outbreak is defined when there are 5 or more suspected measles cases within 4 consecutive weeks or at least 2 measles IgM-positive specimens with an epidemiologic link. A confirmed case was defined as a person with fever and rash, whether or not accompanied by cough, coryza, and conjunctivitis, had an epidemiologically link with index case, with confirmed positive Measles IgM. Result: We investigated 22 (15 male and 7 female) close contacts and we found 2 measles IgM-positive cases from January 18th to February 17th, 2024, in Pakem after an epidemiological investigation with an average incubation period of 8 days. 1 case each occurred in females (AR=14%) and males (AR=7%). The finding of 2 cases with measles IgM-positive and epidemiologic link allows us to declare an outbreak. One of two cases have not received MR immunization. Following the outbreak, measles cases were isolated, given antipyretics, vitamin A supplementation (dose), and Clean and Healthy Living Behaviour education. Conclusion: We confirmed a measles outbreak in Sleman. Case management has been carried out quickly to prevent and control widespread transmission. It is important to improve screening of under-five immunization status by Posyandu.